If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 7x = 3x + 27 Reorder the terms: 7 + 7x = 27 + 3x Solving 7 + 7x = 27 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + 7x + -3x = 27 + 3x + -3x Combine like terms: 7x + -3x = 4x 7 + 4x = 27 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + 4x = 27 + 0 7 + 4x = 27 Add '-7' to each side of the equation. 7 + -7 + 4x = 27 + -7 Combine like terms: 7 + -7 = 0 0 + 4x = 27 + -7 4x = 27 + -7 Combine like terms: 27 + -7 = 20 4x = 20 Divide each side by '4'. x = 5 Simplifying x = 5
| 1+2x+6x=89 | | 5.8x+15=6.8x+9 | | d+6=5d+22 | | 2(2b+3)=3b+12 | | 17=4x+4x+1 | | -2x+2+4x=20 | | 2x-4=11x-94 | | 2.8x=-9.24 | | 4(x+3)=3x+13 | | 2x+19=10x-61 | | 2=-26-10t | | -8x-5+x=3x+9+10x | | 0.52y*2.5=5.1 | | 5a+16=(a+6) | | 4x-9=-41 | | 2x+19=10x-71 | | 7*x+4= | | 6z-11=4z-3 | | 0=-16t^2+176t | | -4-7=5p+11 | | y^2+4y-2=0 | | 6x-6=5x-7 | | 10x-3=8x+3 | | 2-4(b-6)=10 | | 2x^2+2x+5=0 | | 2f+3=11f-25 | | 1.5(5-y)=3y+12 | | 2p+25=6(p-3)-3(4-3p) | | 1g-3+12=3G | | 5t+54=4 | | 14.1=x-7.7 | | 6x+34=8x+12 |